Incentives, administrative capture and preference aggregation in community-based targeting - Abay, Kibrom A.; Berhane, Guush; Gilligan, Daniel O.; Meles, Tensay H.; Tafere, Kibrom (International Food Policy Research Institute, 2025)
Community-based targeting (CBT), which leverages community leaders to identify eligible beneficiaries, is widely used in social protection programs and development interventions, especially in data-scarce settings. Yet, little is known about how these leaders respond to opportunities for potential resource leakages and elite capture, and whether such behavior is moderated by budget constraints or the level of discretion given to leaders. Similarly, how community leaders involved in CBT aggregate individual preferences into collective decisions remains understudied. We conduct a cluster-randomized experiment in 180 Ethiopian villages to study the effects of incentive structures and discretion on administrative capture—defined as funds retained under the disguise of covering “administrative” costs. Local leaders were tasked with allocating real or hypothetical transfer budgets, with discretion to retain up to 10 percent as “administrative costs”. To uncover decision-making and preference aggregation within CBT committees, we elicited these decisions (proposals to retain a portion of the budget) individually as well as collectively. We find that financial incentives significantly increase administrative (elite) capture, and that capture increases with budget size. Group decisions yield higher appropriation than individual proposals, suggesting implicit collusion rather than prosocial restraint in group-based decisions. Moreover, when real stakes are at play, group outcomes are disproportionately shaped by extreme (outlier) preferences, whereas in hypothetical settings without actual transfers, popular preferences dominate. These findings highlight behavioral mechanisms underlying collective decision-making and administrative capture in CBT, which can inform the design of more accountable CBT systems.